Evaluating the impact of coaching skills training on individual and corporate behaviour. Issue 1 (18th February 2019) - Boak, George; Crabbe, Sarah
Abstract : Purpose: The purpose of this paper is to examine the impact of a training intervention designed to develop and encourage the use of coaching skills in a small arts-based organisation and assess the factors that appear to have influenced this impact. Design/methodology/approach: The programme, its effects and factors that influenced its impact were assessed through ongoing feedback and evaluation and through information gathered in a focus group and in one-to-one interviews with participants at the conclusion of the programme. Findings: The programme had individual and organisational benefits, including improved skills in communication and problem-solving and a better understanding of a range of problems affecting the organisation. Factors enabling these benefits included participation of senior managers in the programme and coaching practice that focused on real workplace issues. Factors limiting these benefits included a lack of a clear statement about the purpose of the programme. Research limitations/implications: This relates to a programme within a single organisation, and the findings may not be generalisable. Practical implications: Through training individuals in coaching skills, it is possible to improve the skills needed for cooperative working and joint problem-solving. A corporate training programme in coaching skills can surface a range of organisational problems and enable progress to be made in tackling them. Originality/value: There is little empirical research evaluating the impact of training in coaching skills. This paper identifies how such training can develop leadership skills and indicates practical factors that may enhance or limit the impact of the training.